2016
DOI: 10.1007/s11751-016-0258-2
|View full text |Cite
|
Sign up to set email alerts
|

The management of paediatric diaphyseal femoral fractures: a modern approach

Abstract: The definitive treatment of paediatric femoral diaphyseal fractures remains controversial. Modalities of treatment vary mostly according to age, with fracture pattern and site having a lesser impact. Current evidence is reflective of this variation with most evidence cited by the American Academy of Orthopedic Surgeons being level 4 or 5. The authors present a review of the most up-to-date evidence relating to the treatment of these fractures in each age group. In an attempt to clarify the current trends, we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 63 publications
2
49
0
2
Order By: Relevance
“…Conservative treatments have many advantages being less invasive and practically without risk of soft tissues or growth plate injuries that are described in surgical procedures. On the other hand, conservative treatments present some important limitations: Prolonged skin traction with long hospitalization, significant patient discomfort, difficulties with hygienic care, and long weight-bearing restrictions[ 12 ]. Moreover, casting needs to be done in the operation theatre under general anaesthesia with similar time of surgical procedures, and similar radiation exposure for closed reductions in which sometimes it is necessary to use a specific invasive device[ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conservative treatments have many advantages being less invasive and practically without risk of soft tissues or growth plate injuries that are described in surgical procedures. On the other hand, conservative treatments present some important limitations: Prolonged skin traction with long hospitalization, significant patient discomfort, difficulties with hygienic care, and long weight-bearing restrictions[ 12 ]. Moreover, casting needs to be done in the operation theatre under general anaesthesia with similar time of surgical procedures, and similar radiation exposure for closed reductions in which sometimes it is necessary to use a specific invasive device[ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Today, the trends have veered towards operative fixation due to the benefits of early mobilization and shorter hospital stays. 5,6 Ideally, fixation of paediatric diaphyseal fractures should be able to produce an internal splint that maintains reduction till callus is formed, shares loads and does not endanger the physis or vascularity. Several studies have shown that titanium elastic nailing system/ flexible intramedullary nailing fixation meets these requirements.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%
“…It should be considered that the anatomical segment being examined has peculiar characteristics, which may affect management of the patient. These characteristics include choice if fixation device, surgical timing, patient age, associated lesions, polytrauma (DCO vs ETC treatment), relative frequency of malunions, and atypical fractures [7][8][9][10][11][12] . While it may be invasive and occasionally generate complications such as infections, device, breakage and consolidation alterations, osteosynthesis has numerous advantages, such as early mobilization, a greater stability at the fracture site, and a limited stay in hospital.…”
Section: Treatment Typementioning
confidence: 99%
“…The anterograde insertion point starts with a longitudinal incision proximal to the apex of the greater trochanter that provides for three introduction points of the nailing implant according to the design of the device and the morphological characteris- tics of the patient. They are pyriform fossa, apex of the greater trochanter or laterally to the apex of the greater trochanter checked via fluoroscopic control 6,10,15 . Retrograde access starts with an incision at the level of the patellar tendon to identify the entry point located at the top of the intercondylar fossa through fluoroscopic control in 2 orthogonal views (A-P and L-L) 6,17 .…”
Section: Treatment Typementioning
confidence: 99%